Analyzing Distributed Vibrating Sensing Technologies in Optical Meshes - Saifur Rahman; Farman Ali; Fazal Muhammad; Muhammad Irfan; Adam Glowacz; Mohammed Shahed Akond; Ammar Armghan; Salim Nasar Faraj Mursal; Amjad Ali; Fahad Salem Alkahtani (Micromachines, 2022)
Hundreds of kilometers of optical fibers are installed for optical meshes (OMs) to transmit data over long distances. The visualization of these deployed optical fibers is a highlighted issue because the conventional procedure can only measure the optical losses. Thus, this paper presents distributed vibration sensing (DVS) estimation mechanisms to visualize the optical fiber behavior installed for OMs which is not possible by conventional measurements. The proposed technique will detect the power of light inside the optical fiber, as well as different physical parameters such as the phase of transmitted light inside the thread, the frequency of vibration, and optical losses. The applicability of optical frequency domain reflectometry (OFDR) and optical time-domain reflectometry (OTDR) DVS techniques are validated theoretically for various state detection procedures in optical fibers. The simulation model is investigated in terms of elapsed time, the spectrum of a light signal, frequency, and the impact of many external physical accidents with optical fibers.